The Relation of Governance Principles with Job Satisfaction with the Employees of the Ministry of Education, Sultanate of Oman - Al-Kharusi, Mouza Said (Arab Journal for Sciences and Research Publishing, 2024)
This study aimed to explore the potential relation between governance principles and job satisfaction with the employees of the Ministry of Education, Sultanate of Oman. The analytical descriptive approach is adopted in the study. A questionnaire is established, upon being verified and validated, from literature and previous academic studies to be a research instrument. The findings demonstrate statistical substantial relation between governance principles and job satisfaction with the employees of the Ministry of Education. The Multivariate analysis of variance shows substantial statistical variation of job satisfaction with the “Director General” position. The study recommends conducting further studies on the relation between governance and job satisfaction, as well as the necessity of reviewing the principles and regulations that contribute to job satisfaction.
Keywords: Governance; job satisfaction; Ministry employees